EDUCATING ISLAMIC VALUES THROUGH WIWITAN TRADITION (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
Javanese traditions such as wiwitan have often been perceived as being rooted in Hindu and Buddhist culture, and thus syncretic in nature. As the Javanese people have increasingly emphasized rational–functional values, and as orthodox (Islam as represented by santri has become more mainstream, these traditions have been transformed, allowing the ritual wiwitan to become Islamic tradition, expressing gratitude, alms, family, and tolerance. This article explores the educating processes of Islamic values through wiwitan tradition. Data are collected through observations, interviews, and focus group discussions. The analyses use a descriptive and interpretative approach. The findings have revealed that the wiwitan tradition by East Java's farmers is not a syncretic tradition, as commonly argued, but rather has experienced two important transformations. First, it has become more Islamic as an orthodoxy has become mainstream in Java. Second, the wiwitan tradition has a socio-religious purpose of providing a cultural space for divine (ilahiyah) and humanitarian (insaniyah) values. Wiwitan has thus offered a means of educating Islamic values, because it contains the values of shukr, sadaqah, kinship, and tolerance.